Review of voluntary agreements on energy efficiency: Implications for Asean countries - Jeong Won Kim; Yang Liu (Asian Development Bank Institute (ADBI), 2020)
ASEAN countries need to consider more innovative, market-oriented approaches to accelerate energy efficiency improvement, and well-designed voluntary agreements will play a critical role in raising the awareness of companies and engaging them with the materialization of multiple energy efficiency benefits. This study reviews how successful voluntary agreements on energy efficiency in five countries (the People's Republic of China, Finland, Japan, the Netherlands, and the United Kingdom) achieved their targets in order to draw implications for designing future voluntary agreements in ASEAN countries. We find that three design elements, namely ambitious and realistic target setting, effectively enforceable incentives and penalties, and a strong monitoring and evaluation mechanism, are essential for well-functioning voluntary agreements in these five countries. In addition to these elements, the unique conditions of each country must be considered and transparency must be ensured to maximize the effectiveness of voluntary agreements.
Keywords: Q48; H32; 330; voluntary agreements; energy efficiency; energy efficiency policy; energy-intensive industry; ASEAN